Multi-domain Task-oriented Dialog Challenge II at DSTC9 - Li, Jinchao; Zhu, Qi; Luo, Lingxiao; Liden, Lars; Huang, Kaili; Shayandeh, Shahin; Liang, Runze; Peng, Baolin; Zhang, Zheng; Shukla, Swadheen; Takanobu, Ryuichi; Huang, Minlie; et al. (AAAI-2021 Dialog System Technology Challenge 9 Workshop, 2021)
The paper provides an overview of the “Multi-Domain Task Completion Dialog Challenge II” track at the 9th Dialog System Technology Challenge (DSTC9). Two tasks are introduced in this track. One is end-to-end multi-domain task completion, which focuses on building end-to-end task completion dialog systems. The other is cross-lingual dialog state tracking, which seeks to build a tracker for the target language using the source language resources. We describe the task settings, baselines, evaluation methods, and submission results for both tasks.